Manual Knitting: Who knits a stitch, weaves a tale - Moraes, Mateus Aparecido de; Trauer, Eduardo; Novelli, Daniela; Silveira, Icléia da; Rosa, Lucas da (Seven Editora, 2024)
The manual art of knitted fabric construction, which is called knitting, consists of interlacing a thread or more threads together, with the use of a pair of needles or two ferrules connected by a thread, this tool being known as circular needle and which form fabrics with lacy, smooth or voluminous textures. The aim is to present hand knitting and its relevance to fashion in the historical and social context. The relevance of the research, aims to know the dissemination of manual knitting as a technique and fashion product to the entire Brazilian territory, the research is classified as being of a basic nature, qualitative research, narrative, carried out by literature review with data analysis and discussions. The results of the research indicated that: handicrafts and manual knitting, presented in this study, are segments of expressive value for fashion because it is an artisan widely used in the manufacture of clothing and because it crosses historical moments and is present in the contemporary period. Handicrafts reflect cultural and social identity that are quite attractive in theoretical concepts. Manual knitting indicates a vast unfolding of studies to be developed to notice the creative and authorial expression present in fashion design with evidence both in academia and in society. DOI:https://doi.org/10.56238/sevened2024.007-094